IMPLEMENTASI KEGIATAN LITERASI KEUANGAN SYARIAH MELALUI EXECUTIVE FUNCTION ACTIVITIES PADA ANAK USIA PRA-SEKOLAH DI LINGKUNGAN PIMPINAN DAERAH AISYIAH KABUPATEN PACITAN - Malta Anantyasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Instilling financial literacy from an early age is a strategic step in shaping healthy financial character and habits, especially within the context of sharia values. This study aims to examine the implementation of sharia financial literacy through executive function-based activities for preschool-aged children within the Aisyiyah Regional Leadership of Pacitan Regency. The research method used was descriptive qualitative with a case study approach. Data were collected through observation, in-depth interviews with teachers and parents, and documentation of learning activities. The results showed that the integration of sharia financial literacy in activities that train children's executive functions such as planning, decision-making, and self-control was able to foster children's basic understanding of the concepts of saving, sharing, and money management in accordance with sharia principles. These activities were packaged in the form of role-playing, simple transaction simulations, and stories containing Islamic morals. The conclusion of this study states that the implementation of sharia financial literacy through the executive function activities approach is effective for preschool-aged children and is relevant to the educational values ​​promoted by preschool educational organizations/institutions within the Aisyiyah environment of Pacitan Regency.